KONVENSI DAN INVENSI DALAM CERITA-CERITA KOBOI MUTAKHIR: KAJIAN FORMULA TERHADAP FILM WESTERN PERIODE 1995-2012 - , ANDRIADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The degradation of appreciation toward film Westerns during periode 1995- 2012 is as the backround of this research. It seems that film producers tried to revitalize the elements of Western movies in order to produce more intersesting films with different atmosphere. The problems of this research are to investigate convention, invention, and external factors which influenced the change of formula in Western genre. The problems are investigated by formula theory proposed by Cawelti (1971) and Western formula characteristics proposed by Cawelti (1999). The first step of using this theory is to see narrative structure of Western genre as total system during the periode of 1995-2012. Second, the researcher analyzed the distinctive way in which the Westerns periode 1995-2012 organize these elements into an order pattern or plot to find out regularity elements as continuity of cultural values, and evolutive elements to give new information about cowboy stories. Third, the researcher explored external factors as background of the formula evolution cowboy stories. The result of the research shows that Western movies period 1995-2012 are still based on most of conventional elements which covers: the regularity of theme, setting, complex of characters, type of situations, and pattern of actions. While the evoluted elements came variatively and dynamic based on the development of their era. Plot structures were based on current societyâs taste. The most interesting conclusions are reversal type of esthetic structure in Western films period 1995- 2012: first, the setting showed more modern space and tend to reduce savage space